Pelabelan Sosial dan Respons Komunitas Tasawuf Underground di Ciputat - Ciek Julyati Hisyam; Mayang Puti Seruni; Alma Miftaqiyah; Husnul Khotimah; Kartika Dewi; Muhammad Sufyan Rabbani; Santika Virdi; Sylmi Adila (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This research aims to understand the dynamics of social labeling of the Tasawuf Underground community in Ciputat and how this community responds to the stigma attached by society. This community consists of punk kids who previously received negative stigma due to street lifestyle, psychotropic use, and family conflicts. This research uses a qualitative approach with a case study method and data collection techniques through in-depth interviews, participatory observation, and documentation. The results showed that the negative labeling of punk kids is not only based on deviant behavior, but is more influenced by appearances that do not conform to dominant norms. The Tasawuf Underground Community provides a safe space for the social reintegration process through a tasawuf-based spiritual approach, moral development, and job training. The theory of labeling is used to analyze how the identity of punk kids is renegotiated through community support, behavior change, and resistance to stigma. This research concludes that the social reintegration of punk kids depends not only on individual change, but also on changing the paradigm of society in seeing the potential of the future, not the past. The Tasawuf Underground community plays an important role as a reframing agent that allows the redefinition of the identity of punk kids from being labeled deviant to socially and spiritually accepted individuals.